Penafsiran Ayat-Ayat Hoaks Perspektif Muhammad Husain Thabathabai: Solusi Kerukunan Masyarakat dalam Beragama - Nurul Khair; Alfiyah (Studia Quranika, 2023)
In terms of discourse, it is known that hoaxes are one of the main problems in the creation of intolerance and acts of violence in the paradigm of religious people. In the Indonesian contest, it is realized that the problem of intolerance is based on an individual's lack of knowledge of beliefs outside their beliefs, thus influencing violent behavior and restrictions on religious expression in the life of religious communities. This can be proven through SETARA Institute data which states that from 2018-2020, cases of religious intolerance and violence in Indonesia have increased; to 202, 327, and 422. An increase in cases necessitates mutual suspicion and hostility which has implications for the decline in the value of unity and thus threatens the integrity of the Unitary State of the Republic of Indonesia. This paper is a review of the literature on Muhammad Husain Thabathabai's thoughts regarding the interpretation of hoax verses which are studied through his main work, entitled "Tafsīr al-Mīzān". By using an analytical descriptive approach. The results of this paper, that to overcome the spread of hoaxes, Muhammad Husain Thabathabai through "Tafsīr Mīzān" explains 4 terms of hoax in the Koran, including; ifkun, Iftirā, kidzb, and buhtān to describe the dangers of hoaxes in human life. Furthermore, Muhammad Husain Thabatahabi offers 3 ways to avoid hoaxes to build religious harmony during the Covid-19 pandemic, including; critical thinking, introspection, and staying away from assumptions or prejudice.